Упровадження здоров'язбережувального виховання в польських школах - Інна Мордвінова (Pavlo Tychyna Uman State Pedagogical University, 2012)
У статті розглянуто періоди історичного розвитку та впровадження здоров'язбережувального виховання в польських школах. З'ясовано причини і визначено передумови появи модуля «Навчання здоров'я» на всіх ступенях польської освіти. Висвітлено основні закони та нормативні документи, які обгрунтовують здоров'язбережувальне виховання учнів в різні вікові періоди. В статье рассмотрены периоды исторического развития и внедрения здоровьесберегающего воспитания в польских школах. Охарактеризованы особенности развития исторических периодов и этапов здоровьесберегающего воспитания. Выяснены причины и описаны факторы, которые стали предпосылкой возникновения модуля «Обучение здоровья» во всех отраслях образования. Изучение этого модуля осуществляется в рамках элективных курсов в области физического воспитания. Раскрыты основные составляющие здоровья, которые стали причиной появления здоровьесберегающего воспитания в Польше. Освещены основные законы и нормативные документы, раскрывающие здоровьесберегающее воспитание в различных возрастных периодах. Определена основная цель и задания образовательных реформ в Польше, в частности: изменение системы образования, увеличение продолжительности обучения в школе, введение новых учебных дисциплин в учебные программы и принятие ряда законов, проектов по здоровьесбережению подрастающего поколения This article is devoted to the period of historical development and implementation of health-saving education in Polish schools. Was characterized the features of historical periods and stages of health-saving education. Was describes the causes and factors that are prerequisites of the module «Education of Health» at all levels of education. The study of this module is part of elective courses in physical education. Was solved the basic determinants of health that are prerequisite of health-saving education in Poland. Was disclosed the basic laws and regulations that reveal of health-saving education in different age periods. The basic goals and objectives of educational reform in Poland - change the education system, increasing the duration of schooling, the introduction of new disciplines to the curriculum and a series of laws of health projects on the younger generation. I period - reconstruction (to 1864) - contributed to strengthening national ideas that became the basis for the creation of new independent European states. II period - pioneers (1865-1896 years) - the organization of summer camps for children and gymnastic societies. Conduct educational activities for the development of education and health-saving techs investment. III period - created organizations movement of hygiene (1897-1898 years) - was the development of health care in Poland. IV period - founding Warsaw`s societies of hygiene (1898-1918 years) - creation of infrastructure and health institutions for children, a combination of medical clinics and children's school. V period - the era of the birth of health-saving education in Poland (1900-1979 years) -  introduction of health-saving education in the curricula of all types of schools. VI period - the phase of stagnation (80-ies of XX century). VII period - educational reforms (1990-2005 years of XX century) - was changed the education system, increasing the duration of schooling, the introduction of new disciplines to the curriculum and the adoption of several laws and projects of the health-saving of younger generation. VIII period - development of health-saving education in Poland -  Implementation of educational, training and health-saving programs, printing literature about this themes. Literature review and summarize the experience of researchers give to conclude that educational institutions remains a major social institution that gives children a basic education and training, and solves the problem of educating and development today's students. Expounded material allows to conclude that there is a need to improve the professional training of primary school teachers and disclosure of normative and organizational framework of health-saving in schools of Poland.